A modified synchronverter for a weak grid with virtual power circles‐based PQ decoupling scheme - Daniel Angelo Kisinga; Peter Makolo; Paul Trodden (IET Renewable Power Generation)
Abstract The high penetration of renewable energy sources (RES) results in a low‐inertia, weak power grid. To mitigate this and restore system inertia, it has been widely proposed to operate the inverters of RES units to mimic synchronous generators; this technology is known as a virtual synchronous generator (VSG). In weak grids there is, however, strong coupling between active power (P) and reactive power (Q), and any VSG technique therefore requires PQ decoupling in order to operate effectively. This article proposes a new PQ decoupling technique based on the transformation of the PQ power circle of a VSG connected to a weak grid: first, the power circle is translated from its designed position to that of a conventional synchronous generator (SG) connected to a strong grid, achieving partial PQ decoupling. Then, to achieve full PQ decoupling, the authors propose further to modulate the radius of the translated PQ power circle; this is achieved using a series resistance‐capacitance–inductance (RCL) circuit which is virtually implemented in the VSG controller. The efficacy of the proposed scheme is validated using a modified synchronverter connected to the weak grid in representative loading scenarios. It is demonstrated that the technique achieves a decoupled PQ control for the synchronverter connected in a weak grid. Moreover, the modified synchronverter is capable of supporting frequency and voltage regulation in the grid without inducing large transient grid currents during mild frequency and voltage variations.